Association of preexisting hypertension with the morality in patients with systolic heart failure in Taiwan: The TSOC-HFrEF registry - Meng, Fan-Chun (Indian Heart J, 2018)
PURPOSE: To investigate the association of preexisting hypertension at admission with the mortality in patients with systolic heart failure (HF). METHOD: We prospectively investigated the association of preexisting hypertension with the mortality among 1351 patients with HF in Taiwan during an average 12 months (range: 8 months–18 months) follow-up period. A multivariate cox regression analysis for the overall cohort and a subgroup analysis by age were performed. RESULTS: After adjustment for all potential risk factors, the associations of preexisting hypertension with cardiovascular mortality were significantly reduced in the overall cohort and those aged less than 65 years (hazard ratios (HR): 0.53, 95% confidence intervals (CI): 0.33–0.84, and 0.28, 95% CI: 0.11–0.67, respectively). However, the associations with all-cause mortality were not significantly different in these two groups (HR: 0.77, 95% CI: 0.54–1.09, and 0.59, 95% CI: 0.32–1.07, respectively). Furthermore, the associations were all nonsignificant in the patients aged older than 65 years. CONCLUSION: Preexisting hypertension have an inverse association with cardiovascular mortality in the Asian patients with systolic HF, particularly for those with younger ages.